2022
DOI: 10.3390/met12071081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wall Thickness and Surface Conditions on Creep Behavior of a Single-Crystal Ni-Based Superalloy

Abstract: The influence of wall thickness and specimen surface on the creep behavior of the single-crystal nickel-based superalloy MAR M247LC is studied. Specimens with wall thicknesses of 0.4, 0.8, 1 and 2 mm, with and without casting surface, are compared to specimens of the same wall thickness prepared from bulk material. Creep behavior turned out to be independent from surface conditions even for the thinnest specimens. The thickness debit effect is not pronounced for short creep rupture times (≤100 h at 980 °C), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Importantly, it should be emphasized that the casting pores are all eliminated in the two alloys with the help of HIP heat treatment. The presence of microporosity will harm the properties of Mar-M247, resulting in the scatter of creep performance [28]. The application of HIP heat treatment ensured the subsequent creep test results were not influenced by casting pores.…”
Section: As-cast and Heat-treated Microstructuresmentioning
confidence: 99%
“…Importantly, it should be emphasized that the casting pores are all eliminated in the two alloys with the help of HIP heat treatment. The presence of microporosity will harm the properties of Mar-M247, resulting in the scatter of creep performance [28]. The application of HIP heat treatment ensured the subsequent creep test results were not influenced by casting pores.…”
Section: As-cast and Heat-treated Microstructuresmentioning
confidence: 99%
“…the creep lifetimes of DD6 increased with the decrease of the specimen thickness slightly. Most of the investigations focused on thin‐walled specimens machined from bulk materials 32–34 . Through the creep experiments of casting specimens and machined specimens of nickel‐based single crystal superalloy MAR M247LC, Körber et al 34 found that there were differences in thickness debit effect of MAR M247LC specimens prepared in different ways, and the microstructure difference (such as initial porosity) caused by different processing methods is an important reason for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigations focused on thin-walled specimens machined from bulk materials. [32][33][34] Through the creep experiments of casting specimens and machined specimens of nickel-based single crystal superalloy MAR M247LC, Körber et al 34 found that there were differences in thickness debit effect of MAR M247LC specimens prepared in different ways, and the microstructure difference (such as initial porosity) caused by different processing methods is an important reason for this phenomenon. Texier et al 35 conducted high-temperature creep experiments with thin-wall specimens (50-200 μm), and the experimental results revealed heterogeneities in creep behavior at a mesoscopic scale, attributed to differences in creep strength between dendrite cores and interdendritic regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of rhenium (Re) can significantly impede the growth of the γ′ phase and contribute to microstructural stability [ 26 ]. It is worth noting that previous investigations into the deformation mechanisms of SX superalloys during creep have mostly focused on temperatures below 1100 °C [ 27 ]. The behavior and deformation mechanisms during creep at temperatures exceeding 1100 °C have been rarely explored, despite the fact that Re addition at these temperatures promotes the precipitation of topologically close-packed (TCP) phases [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%